2017
DOI: 10.1002/star.201600203
|View full text |Cite
|
Sign up to set email alerts
|

Amylose–lipid complex production and potential health benefits: A mini‐review

Abstract: Amylose-lipid complexes (ALCs) are classified as resistant starch types III or V. This paper reviews the ALCs production methods and health benefits and provides an outlook of the future. ALCs can be produced in the lab to obtain pure compounds; lipids (mostly fatty acids or monoacyl glycerol) are added to starch and heat-processed in excess water by extrusion cooking or steam-jet cooking to produce the starch-lipid complexes. However, information concerning the occurrence of ALCs in foods such as cereals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(72 citation statements)
references
References 55 publications
0
65
1
1
Order By: Relevance
“…Starch–lipid complexes have been studied extensively and their effects on the functional properties and nutritional value of starch have been characterized (Obiro, Sinha Ray, & Emmambux, 2012b; Panyoo & Emmambux, 2017; Putseys, Lamberts, & Delcour, 2010). The formation of starch–lipid complexes in food systems reduces the swelling power and solubility of starch, retards starch gelatinization and retrogradation, and slows down its rate of enzymic digestion (Copeland, Blazek, Salman, & Tang, 2009; Putseys et al., 2010; Wang & Copeland, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Starch–lipid complexes have been studied extensively and their effects on the functional properties and nutritional value of starch have been characterized (Obiro, Sinha Ray, & Emmambux, 2012b; Panyoo & Emmambux, 2017; Putseys, Lamberts, & Delcour, 2010). The formation of starch–lipid complexes in food systems reduces the swelling power and solubility of starch, retards starch gelatinization and retrogradation, and slows down its rate of enzymic digestion (Copeland, Blazek, Salman, & Tang, 2009; Putseys et al., 2010; Wang & Copeland, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The values obtained in this study were relatively higher than those reported for starches from rice (21.88%-22.64%) by Ashogbon and Akintayo (2013). The Amylose-lipid complexes are potential fat replacers in food (Panyoo & Emmambux, 2017). The high amylose content observed in this study showed that the starch could be used to partially replace fat in fat-rich food and as emulsion stabilizer.…”
Section: Total Amylose Free Amylose and Lipidcomplexed Amylosementioning
confidence: 72%
“…Among the health benefits of amylose–lipid complexes (resistant starch type IV or V) include improvement of colonic health microflora, management of diabetes, lower glycemic index, and blood cholesterol levels, reduced bilestone formation, and increased mineral absorption. Amylose–lipid complexes are potential fat replacers in food (Panyoo & Emmambux, ). The high amylose content observed in this study showed that the starch could be used to partially replace fat in fat‐rich food and as emulsion stabilizer.…”
Section: Resultsmentioning
confidence: 99%
“…The V‐amylose structure has been a relatively mature system to encapsulate sensitive compounds for many years . Amylose in starch forms double helices in water through hydrogen bonds; whereas, with the suitable ligands like iodine, flavoring compounds, lipids, amylose rearranges to single helices conformation which is hydrophilic on the outside and hydrophobic inside . The formation of V‐amylose complexes could also reduce the digestibility of starch and postprandial hyperglycemia when consumed by diabetics .…”
Section: Introductionmentioning
confidence: 99%